FENOMENA KIMCIL DI KOTA BANYUWANGI (Analisis Prostitusi Terselubung Berkedok Pelajar Sekolah) - Dea Denta Tajwidi (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2017)
Kimcil stands for little kimpet or it can also be a small knot (some even interpret it as a little cimplicant). In Indonesian kimpet means small vagina. Kimcil is a teenager aged 14-19 years who on average is still a junior to high school student with a fashionable appearance and promiscuity which aims to attract many men and is willing to sell his body to get a reward in the form of material and services according to what was agreed upon. The emergence of the Kimcil phenomenon among students indicates a speciality in the world of prostitution. This black business makes commodities that are considered very profitable for them. The specific purpose of writing this article is to 1) Know and analyze the background of the emergence of Kimcil prostitution in the city of Banyuwangi, and 2) Know and analyze the effects of Kimcil prostitution in the City of Banyuwangi, both the impact on Kimcil prostitutes and the impact on the wider community and especially for Kimcil consumers. The research method used is a qualitative research method with steps including determining the location of research, research subjects, data collection methods, data validity testing methods and data analysis. The background of the emergence of Kimcil prostitution in the city of Banyuwangi is 1) family factors, 2) economic factors, 3) social factors, 4) factors of sex experience, 5) mass media factors, 6) factors of the high cost of education.